2023
DOI: 10.1002/adtp.202200331
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomal Nanoformulations for Combinational Photothermal Therapy of Fungal Keratitis

Abstract: Fungal keratitis/mycotic keratitis or keratomycosis, is characterized by the inflammation of underlying stroma of corneal epithelium due to fungal infection. Multi‐drug resistance and subsequent recurrence of infection limits the clinical outcomes of anti‐fungal agents such as Amphotericin B and Natamycin; and therefore, demands research on newer anti‐microbial strategies. In this study, the authors have synthesized and characterized ethosomes (IAEs) encapsulating a NIR dye, Indocyanine green (ICG), and an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The same procedure was used for untreated groups. [ 74,75 ] After the incubation, the variation in the number of spots was assessed. Statistical analysis was conducted using a one‐way analysis of variance (ANOVA) to determine the significance of the results.…”
Section: Methodsmentioning
confidence: 99%
“…The same procedure was used for untreated groups. [ 74,75 ] After the incubation, the variation in the number of spots was assessed. Statistical analysis was conducted using a one‐way analysis of variance (ANOVA) to determine the significance of the results.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their smaller size and elastic shape compared to typical liposomes, they enable local transport of both hydrophilic and hydrophobic active molecules and can enhance drug penetration or localization [ 78 , 79 ]. The comparative study revealed that ethosomal formulations exhibited more drug penetration into the cornea than liposomal formulations [ 80 ].…”
Section: Vesicular Systemsmentioning
confidence: 99%
“…In research, Sushma et al (2023) designed ethosomes (IAEs) for a combination photothermal therapy of fungal keratitis that contains the near-infrared (NIR) dye, Indocyanine green (ICG), and the anti-fungal drug Amphotericin B [ 80 ]. Ethosomes were prepared by the TFH method.…”
Section: Vesicular Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering biocompatibility and immunogenicity, several studies suggest a generally good biocompatibility profile of ethosomes; however, in some cases, they have been found to cause immune stimulation. A study devoted to the topical application of ethosomes loaded with an antifungal drug (amphotericin B) and a photoresponsive dye (indocyanine green) for the treatment of fungal infection in the cornea [ 60 ] showed high biocompatibility following tests on human corneal epithelial (HCE) cells and basing on a Draize eye test model in rabbits. In another study, ethosomes were evaluated on dendritic cells (DCs) in order to analyze their immune stimulatory effect.…”
Section: Ethosomal Delivery Systemsmentioning
confidence: 99%